Evaluasi Pelaksanaan Program Sentra Industri Kerupuk Ikan Di Kelurahan Sei Lekop Kecamatan Bintan Timur Oleh Dinas Koperasi Usaha Mikro Perindustrian Dan Perdagangan Kabupaten Bintan - Delia Delia Alfrianty; Rudi Subiyakto; Jamhur Poti (Bahasa Indonesia, 2023)
The fish cracker business is one of the focuses of the Small and Medium Industries (IKM) in Bintan Regency, especially the Sei Lekop Village. The fish cracker business has been carried out by community groups to improve the economy of the surrounding community. However, there are still several problems, including limited storage space (cool storage/cooling box), limited space for drying, and a lack of manpower in producing fish crackers. This study aims to evaluate the implementation of the fish cracker industry center program in Sei Lekop Village, East Bintan District, by the Office of Cooperative Micro Enterprises, Industry and Trade, Bintan Regency. The research method uses descriptive research with a qualitative approach. Result of this research is that implementation of the fish cracker industry center program in the Sei Lekop Village has been running according to the objective, namely to be able to improve the community's economy. It is hoped that this program can continue with the presence of assistants from the relevant agencies to assist business actors, both technical and non-technical.